Pró-reitores do IFES : percursos formativos e competências gerenciais - Oliveira, Líssia Pignaton de (2017)
This research aimed to draw a profile of strategic level managers from a federal institution, usually professors are indicated for this functions, accumulating together the managerial activities and the academic ones, without opportunity to do an specific training in management area. In the theoretical contribution is exposed a brief context about conceptions and attributes of competence, management by competencies in the public sector, and the importance of the manager and the decision making. Understanding that managerial skills can represent an improvement in management, as the mapped competences can serve as a subsidy for implementation of training based on the actual needs of these individuals, sought to map in the perception of the pro-rectors of Ifes the necessary competencies to occupy manager functions to development of their activities. The subjects of the research were 11 managers who occupy or occupied the function of Pro-Rector in the Ifes and two instruments of data collection were used: questionnaire (composed of three parts containing questions concerning the sociodemographic profile, the evaluation of the competences perceived in itself and the perception as to the degree of importance of the competences for the exercise of the function of Pro-Rector) and semi-structured interview. The questionnaire data were analyzed from the Servqual Model and the interviews by the technique of content analysis with the support of IRAMUTEQ software. A table was presented with the gaps of competences to be improved in relation to their attributes in the (real) function performance, their expectation in relation to the exercise of the pro-rector function (desired) with a comparison of the averages in relation to the competency, ability and attitude, the relationship of the gaps with the academic formation and the managerial experience, as well as the main difficulties and challenges of the function of Pro-Rector. Finally, a proposal for a managerial development program is presented, in view of the need identified from the data analysis